Smooth muscle cell-specific Notch1 haploinsufficiency restricts the progression of abdominal aortic aneurysm by modulating CTGF expression. - Jaspreet Sachdeva; Advitiya Mahajan; Jeeyun Cheng; Jeremy T Baeten; Brenda Lilly; Helena Kuivaniemi; Chetan P Hans (PLoS ONE, 2017)
Infiltration of macrophages and apoptosis of vascular smooth muscle cells (VSMCs) promote the development of abdominal aortic aneurysm (AAA). Previously, we demonstrated that global Notch1 deficiency prevents the formation of AAA in a mouse model. Herein, we sought to explore the cell-specific roles of Notch1 in AAA development.Cell-specific Notch1 haploinsufficient mice, generated on Apoe-/- background using Cre-lox technology, were infused with angiotensin II (1000 ng/min/kg) for 28 days. Notch1 haploinsufficiency in myeloid cells (n = 9) prevented the formation of AAA attributed to decreased inflammation. Haploinsufficiency of Notch1 in SMCs (n = 14) per se did not prevent AAA formation, but histoarchitectural traits of AAA including elastin degradation and aortic remodeling, were minimal in SMC-Notch1+/-;Apoe-/- mice compared to Apoe-/- mice (n = 33). Increased immunostaining of the contractile SMC-phenotype markers and concomitant decreased expression of synthetic SMC-phenotype markers were observed in the aortae of SMC-Notch1+/-;Apoe-/- mice. Expression of connective tissue growth factor (CTGF), a matrix-associated protein that modulates the synthetic VSMC phenotype, increased in the abdominal aorta of Apoe-/- mice and in the adventitial region of the abdominal aorta in human AAA. Notch1 haploinsufficiency decreased the expression of Ctgf in the aorta and in vitro cell culture system. In vitro studies on SMCs using the Notch1 intracellular domain (NICD) plasmid, dominant negative mastermind-like (dnMAML), or specific siRNA suggest that Notch1, not Notch3, directly modulates the expression of CTGF.Our data suggest that lack of Notch1 in SMCs limits dilation of the abdominal aorta by maintaining contractile SMC-phenotype and preventing matrix-remodeling.